Binder composition for power storage device, slurry for power storage device electrode, power storage device electrode, and power storage device

By using the aqueous binder composition, environmental and economic problems caused by the formation of crosslinking bodies under alkaline conditions and the use of organic solvents are solved, and an electric storage device electrode with high adhesion, flexibility and cycle characteristics are achieved.

CN119895594APending Publication Date: 2025-04-25ENEOS MATERIALS CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380066336.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-09-08
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the positive electrode slurry is prone to form a crosslinker under alkaline conditions, hindering adhesion, and the use of organic solvents leads to high environmental load and expensive damage removal equipment.

Method used

Using an aqueous binder composition, it contains polymer (A) and liquid medium (B). The polymer (A) contains 15 to 64% of unsaturated carboxylic acid ester repeating units with aliphatic hydrocarbon groups and 35 to 84% of aromatic vinyl compound repeating units. Only one dynamic viscoelastic tan δ peak appears in the range of -50°C to 0°C and 50°C to 150°C.

Benefits of technology

The water-based adhesive composition can improve the adhesion and flexibility of the electrodes of the power storage device, reduce the rise of internal resistance, and improve cycle characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005312346860000281
    Figure BDA0005312346860000281
  • Figure BDA0005312346860000291
    Figure BDA0005312346860000291
  • Figure BDA0005312346860000311
    Figure BDA0005312346860000311
Patent Text Reader

Abstract

Provided is a binder composition for a power storage device, which is an aqueous binder, is capable of producing a power storage device electrode having excellent adhesion and flexibility, and is capable of improving cycle characteristics by reducing an increase in internal resistance of the power storage device. The binder composition for an electricity storage device according to the present invention contains a polymer (A) and a liquid medium (B), and when the total of repeating units contained in the polymer (A) is taken as 100 mass%, the content of the repeating units contained in the polymer (A) is less than or equal to 100 mass%. The polymer (A) contains 15-64 mass% of a repeating unit (a1) derived from an unsaturated carboxylic acid ester having an aliphatic hydrocarbon group (excluding an unsaturated carboxylic acid ester having an alicyclic hydrocarbon group), and 35-84 mass% of a repeating unit (a2) derived from an aromatic vinyl compound. Only one peak of the dynamic viscoelasticity tan [delta] (loss modulus / storage modulus) appears in the range of-50 DEG C to 0 DEG C, and only one peak appears in the range of 50 DEG C to 150 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a binder composition for an electrical storage device, a slurry for an electrical storage device electrode, an electrical storage device electrode, and an electrical storage device. Background Art

[0002] In recent years, as a power source for driving electronic devices, a power storage device having a high voltage and a high energy density is required. As such a power storage device, lithium ion batteries, lithium ion capacitors, etc. are expected.

[0003] The electrode used in such an electric storage device is manufactured by applying a composition containing an active material and a polymer functioning as a binder (slurry for electric storage device electrodes) on the surface of a current collector and drying it. As the properties required of the polymer used as a binder, the ability of the active materials to bind to each other and the ability of the active material to fit the current collector can be cited. In addition, the anti-powdering property that the fine powder of the active material does not fall off from the active material layer when cutting the coated and dried composition coating (hereinafter also referred to as "active material layer") can also be cited. Such a binder material exhibits good adhesion, and by reducing the internal resistance of the battery caused by the binder material, it is possible to impart good charge and discharge characteristics to the electric storage device.

[0004] It should be noted that it is known from experience that the bonding ability of the above-mentioned active materials to each other, the adhesion ability of the active materials to the collector, and the anti-powdering performance are roughly proportional. Therefore, in this specification, the term "adhesion" is sometimes used to collectively represent these performances.

[0005] Recently, in order to produce electrochemical devices with excellent capacity and charge-discharge cycle characteristics, the use of positive electrode active materials with high reactivity with water is being studied. Moreover, polyvinylidene fluoride (PVDF) is the most widely used as an organic solvent-based binder for storage device electrodes. Although PVDF has good adhesion and oxidation resistance, it contains fluorine atoms, has a high environmental load and the instability of raw material supply is gradually manifested (for example, refer to Patent Document 1).

[0006] Under such background, various binder materials have been proposed to solve the many problems of positive electrode slurry (for example, refer to Patent Documents 1 and 2).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 10-298386

[0010] Patent Document 2: Japanese Patent Application Publication No. 2019-194944 Summary of the invention

[0011] However, in the method of using the PVDF used in the past or the positive electrode slurry containing the sulfonated PVDF disclosed in the above-mentioned patent document 1, it is known that a cross-linked body is formed with the removal of HF, especially under alkaline conditions. If the cross-linked body is formed in the positive electrode slurry, it sometimes hinders the adhesion. In addition, in the positive electrode slurry containing the PVDF used in the past, due to the use of aprotic polar solvents such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone, there is a problem of high environmental load and a large amount of cost required for detoxification equipment and waste liquid treatment. Therefore, in the positive electrode slurry, the demand for an aqueous binder that can prepare a mixture slurry without using an organic solvent is gradually increasing.

[0012] Several aspects of the present invention provide a binder composition for an electrical storage device, which is an aqueous binder capable of producing an electrical storage device electrode having excellent adhesion and flexibility and capable of reducing an increase in internal resistance of the electrical storage device to improve cycle characteristics.

[0013] The present invention has been made to solve at least a part of the above-mentioned problems, and can be implemented as any of the following aspects.

[0014] One embodiment of the binder composition for an electrical storage device according to the present invention is

[0015] Containing a polymer (A) and a liquid medium (B),

[0016] When the total amount of the repeating units contained in the polymer (A) is 100% by mass, the polymer (A) contains:

[0017] Repeating units (a1) derived from unsaturated carboxylic acid esters having an aliphatic hydrocarbon group (excluding unsaturated carboxylic acid esters having an alicyclic hydrocarbon group) 15 to 64% by mass

[0018] Repeating units (a2) derived from aromatic vinyl compounds: 35 to 84% by mass;

[0019] The peak top of tan δ (loss elastic modulus / storage elastic modulus) of the dynamic viscoelasticity of the polymer (A) appears only once in the range of -50°C to 0°C and only once in the range of 50°C to 150°C.

[0020] In one embodiment of the above-mentioned binder composition for electrical storage devices,

[0021] The polymer (A) may further contain 0.1 to 10% by mass of a repeating unit (a3) ​​derived from an unsaturated carboxylic acid.

[0022] In one embodiment of the above-mentioned binder composition for electrical storage devices,

[0023] When the polymer (A) is immersed in a solvent composed of propylene carbonate and diethyl carbonate in a volume ratio of 1:1 at 70° C. for 24 hours, the swelling ratio of the electrolyte solution is 120% to 300% by mass.

[0024] In one embodiment of the above-mentioned binder composition for electrical storage devices,

[0025] The polymer (A) is a polymer particle.

[0026] The number average particle size of the polymer particles is 50 nm to 500 nm.

[0027] In one embodiment of the above-mentioned binder composition for electrical storage devices,

[0028] The surface acid amount of the polymer particles is 0.05 mmol / g to 2 mmol / g.

[0029] One embodiment of the slurry for electrical storage device electrodes according to the present invention is:

[0030] The binder composition for an electrical storage device according to any one of the above aspects and an active material are contained.

[0031] In one embodiment of the above-mentioned slurry for electrical storage device electrodes,

[0032] The active material may contain at least one selected from the group consisting of an olivine-type lithium-containing phosphate compound, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, and ternary nickel-cobalt-manganese oxide.

[0033] In one embodiment of the above-mentioned slurry for electrical storage device electrodes,

[0034] A carbon material may be contained as the above-mentioned active material.

[0035] One embodiment of an electrical storage device electrode according to the present invention is as follows:

[0036] The present invention comprises a current collector and an active material layer, wherein the active material layer is formed by applying the slurry for a storage device electrode of one embodiment described above on a surface of the current collector and drying the slurry.

[0037] One embodiment of the power storage device according to the present invention is as follows:

[0038] An electric storage device electrode according to one aspect described above is provided.

[0039] The binder composition for an electrical storage device according to the present invention may be an aqueous binder, which improves the adhesion and flexibility of an electrical storage device electrode and can reduce an increase in the internal resistance of the electrical storage device to improve cycle characteristics. DETAILED DESCRIPTION

[0040] Hereinafter, preferred embodiments of the present invention will be described in detail. It should be noted that the present invention is not limited to the embodiments described below, and should be understood to include various modifications that can be implemented within the scope of the present invention.

[0041] In the present specification, “(meth)acrylic acid” means “acrylic acid” or “methacrylic acid”, “~(meth)acrylate” means “~acrylate” or “~methacrylate”, and “(meth)acrylamide” means “acrylamide” or “methacrylamide”.

[0042] In the present specification, a numerical range described as "X to Y" is to be interpreted as including the numerical value X as a lower limit and including the numerical value Y as an upper limit.

[0043] 1. Binder composition for power storage device

[0044] The binder composition for storage devices according to one embodiment of the present invention contains a polymer (A) and a liquid medium (B). Regarding the above-mentioned polymer (A), when the total of the repeating units contained in the polymer (A) is set to 100% by mass, it contains: 15 to 64% by mass of repeating units (a1) from unsaturated carboxylates having aliphatic hydrocarbon groups (excluding unsaturated carboxylates having alicyclic hydrocarbon groups), and 35 to 84% by mass of repeating units (a2) from aromatic vinyl compounds. In addition, the peak of tanδ (loss elastic modulus / storage elastic modulus) of the dynamic viscoelasticity of the above-mentioned polymer (A) appears only once in the range of -50°C to 0°C, and only once in the range of 50°C to 150°C.

[0045] The binder composition for storage devices according to the present embodiment can be used as a material for preparing storage device electrodes (active material layers) with improved bonding ability between active materials, adhesion between active materials and current collectors, anti-powder shedding, and flexibility of electrodes, and can also be used as a material for forming a protective film for suppressing short circuits caused by dendrites generated during charging and discharging. The components contained in the binder composition for storage devices according to the present embodiment are described in detail below.

[0046] 1.1. Polymer (A)

[0047] The binder composition for an electrical storage device according to the present embodiment contains a polymer (A). The polymer (A) may be in a latex state dispersed in a liquid medium (B) or may be in a state dissolved in the liquid medium (B).

[0048] Hereinafter, the repeating units constituting the polymer (A), the physical properties of the polymer (A), and the method for producing the polymer (A) will be described in this order.

[0049] 1.1.1. Repeating units constituting polymer (A)

[0050] Regarding the polymer (A), when the total of the repeating units contained in the polymer (A) is set to 100% by mass, the repeating units (a1) (hereinafter, also referred to as "repeating units (a1)") derived from an unsaturated carboxylic acid ester having an aliphatic hydrocarbon group (excluding unsaturated carboxylic acid ester having an alicyclic hydrocarbon group) contain 15 to 64% by mass, and the repeating units (a2) (hereinafter, also referred to as "repeating units (a2)") derived from an aromatic vinyl compound contain 35 to 84% by mass. In addition to the repeating units (a1) and the repeating units (a2), the polymer (A) may also contain repeating units derived from other monomers copolymerizable with these.

[0051] 1.1.1.1. Repeating unit (a1) derived from an unsaturated carboxylic acid ester having an aliphatic hydrocarbon group

[0052] In the present invention, the polyfunctional (meth) acrylate and the unsaturated carboxylic acid ester with alicyclic hydrocarbon group described later are not included in the "unsaturated carboxylic acid ester with aliphatic hydrocarbon group". When the total of the repeating units contained in the polymer (A) is set to 100% by mass, the content ratio of the repeating unit (a1) from the unsaturated carboxylic acid ester with aliphatic hydrocarbon group is 15 to 64% by mass. The lower limit of the content ratio of the repeating unit (a1) is preferably 15% by mass, more preferably 18% by mass, and particularly preferably 20% by mass. The upper limit of the content ratio of the repeating unit (a1) is preferably 64% by mass, more preferably 60% by mass, and particularly preferably 55% by mass. By containing the repeating unit (a1) within the above range, the polymer (A) can produce an active material layer and a protective film with good dispersibility and homogeneity of the active material and filler, and because the flexibility of the electrode is also improved, the structural defects of the electrode plate disappear, showing good charge and discharge characteristics. In addition, stretchability can be imparted to the polymer (A) covering the surface of the active material, and the stretchability of the polymer (A) can improve the adhesion, thereby showing good charge and discharge durability characteristics.

[0053] The unsaturated carboxylic acid ester having an aliphatic hydrocarbon group is not particularly limited, but is preferably a (meth)acrylate. Specific examples of such (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, and the like, and one or more selected from these may also be used. Among these, one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred, and one or more selected from n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are more preferred.

[0054] 1.1.1.2. Repeating units derived from aromatic vinyl compounds (a2)

[0055] When the total of the repeating units contained in the polymer (A) is set to 100% by mass, the content ratio of the repeating unit (a2) from the aromatic vinyl compound is preferably 35 to 84% by mass. The lower limit of the content ratio of the repeating unit (a2) is preferably 35% by mass, more preferably 40% by mass, and particularly preferably 45% by mass. The upper limit of the content ratio of the repeating unit (a2) is preferably 84% by mass, more preferably 80% by mass, and particularly preferably 75% by mass. By containing repeating units (a2) within the above range, the polymer (A) can suppress the fusion of the polymers (A) dispersed in the active material layer and improve the permeability of the electrolyte, thereby reducing the rise of the internal resistance, showing good repeated charge and discharge characteristics. Furthermore, it is possible to obtain a storage device electrode having good adhesion and excellent adhesion to graphite, etc. used as an active material.

[0056] The aromatic vinyl compound is not particularly limited, and examples thereof include styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, chlorostyrene, divinylbenzene, and the like. One or more selected from these may be used.

[0057] 1.1.1.3. Other repeating units

[0058] In addition to the repeating units (a1) and (a2), the polymer (A) may contain repeating units derived from other monomers copolymerizable with these. Examples of such repeating units include repeating units (a3) ​​derived from unsaturated carboxylic acids (hereinafter, also referred to as "repeating units (a3)"), repeating units (a4) derived from polyfunctional (meth)acrylates (hereinafter, also referred to as "repeating units (a4)"), repeating units (a5) derived from other unsaturated carboxylic acid esters (hereinafter, also referred to as "repeating units (a5)"), repeating units (a6) derived from (meth)acrylamide (hereinafter, also referred to as "repeating units (a6)"), repeating units (a7) derived from α,β-unsaturated nitrile compounds (hereinafter, also referred to as "repeating units (a7)"), repeating units (a8) derived from compounds having sulfonic acid groups (hereinafter, also referred to as "repeating units (a8)"), and repeating units derived from cationic monomers.

[0059] <Repeating unit (a3) ​​derived from unsaturated carboxylic acid>

[0060] The polymer (A) may contain a repeating unit (a3) ​​derived from an unsaturated carboxylic acid. The unsaturated carboxylic acid is not particularly limited, and examples thereof include monocarboxylic acids and dicarboxylic acids (including anhydrides) such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, and itaconic acid, and one or more selected from these can be used. As the unsaturated carboxylic acid, one or more selected from acrylic acid, methacrylic acid, and itaconic acid are preferably used.

[0061] When the total of the repeating units contained in the polymer (A) is set to 100% by mass, the content ratio of the repeating unit (a3) ​​derived from the unsaturated carboxylic acid is preferably 0.1 to 10% by mass, and more preferably 1 to 8% by mass. By containing the repeating unit (a3) ​​within the above range, the polymer (A) can produce an active material layer and a protective film with good dispersibility and homogeneity of the active material and filler, so that the structural defects of the electrode plate disappear, showing good charge and discharge characteristics.

[0062] <Repeating unit (a4) derived from polyfunctional (meth)acrylate>

[0063] The polymer (A) may contain a repeating unit (a4) derived from a polyfunctional (meth)acrylate. When the polymer (A) contains the repeating unit (a4), the electrolyte swelling rate of the polymer (A) in the electrolyte may be more easily suppressed.

[0064] In the present invention, "multifunctional" means that the (meth)acrylate has, in addition to one polymerizable double bond, one or more functional groups selected from the group consisting of a polymerizable double bond and an epoxy group.

[0065] Specific examples of the multifunctional (meth)acrylate include glycidyl (meth)acrylate, allyl (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethylene glycol di(meth)acrylate, and the like, and one or more selected from these can be used. Among these, one or more selected from allyl (meth)acrylate and ethylene glycol di(meth)acrylate are preferred, and allyl (meth)acrylate is particularly preferred.

[0066] When the total amount of repeating units contained in the polymer (A) is 100% by mass, the content of the repeating unit (a4) derived from the multifunctional (meth)acrylate is preferably 0.1 to 10% by mass, and more preferably 1 to 8% by mass. When the polymer (A) contains the repeating unit (a4) within the above range, it is easier to suppress the electrolyte swelling rate of the polymer (A) in the electrolyte, which is preferred.

[0067] <Repeating units (a5) derived from other unsaturated carboxylic acid esters>

[0068] The polymer (A) may contain repeating units (a5) derived from other unsaturated carboxylic acid esters. In the present invention, "other unsaturated carboxylic acid esters" refer to unsaturated carboxylic acid esters other than the above-mentioned unsaturated carboxylic acid esters having an aliphatic hydrocarbon group and the above-mentioned polyfunctional (meth)acrylate.

[0069] As other unsaturated carboxylates, there are no particular limitations, and examples include unsaturated carboxylates having a hydroxyl group, unsaturated carboxylates having a phenoxy group, and the like. As unsaturated carboxylates having a hydroxyl group, examples include 2-hydroxymethyl (meth) acrylate, 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 3-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, 5-hydroxypentyl (meth) acrylate, 6-hydroxyhexyl (meth) acrylate, glycerol mono (meth) acrylate, and the like. As unsaturated carboxylates having a phenoxy group, examples include phenoxydiethylene glycol (meth) acrylate, and the like. For other unsaturated carboxylates, one or more selected from these can be used. Among these, 2-hydroxyethyl (meth) acrylate and glycerol mono (meth) acrylate are preferred. It should be noted that the polymer (A) preferably does not contain repeating units derived from unsaturated carboxylates having an alicyclic hydrocarbon group.

[0070] When the total of the repeating units contained in the polymer (A) is set to 100% by mass, the content ratio of the repeating units (a5) from other unsaturated carboxylates is preferably 0 to 10% by mass, more preferably 1 to 8% by mass. By containing the repeating units (a5) within the above range, the polymer (A) has good dispersibility in the slurry of active materials and fillers. In addition, the softness of the active material layer obtained sometimes becomes appropriate, and the adhesion of the collector to the active material layer is improved.

[0071] <Repeating unit (a6) derived from (meth)acrylamide>

[0072] The polymer (A) may contain a repeating unit (a6) derived from (meth)acrylamide. (Meth)acrylamide is not particularly limited, and examples thereof include acrylamide, methacrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N,N-diethylmethacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, N-hydroxymethylacrylamide, N-hydroxymethylmethacrylamide, diacetoneacrylamide, maleamide, and the like. At least one selected from these may be used.

[0073] When the total of the repeating units contained in the polymer (A) is set to 100% by mass, the content ratio of the repeating unit (a6) from (meth) acrylamide is preferably 0 to 5% by mass, more preferably 1 to 4% by mass. By containing the repeating unit (a6) in the above range, the polymer (A) sometimes has good dispersibility in the slurry of the active material and the filler. In addition, the softness of the active material layer obtained is sometimes appropriate, and the adhesion of the collector to the active material layer is improved.

[0074] <Repeating unit (a7) derived from <α,β-unsaturated nitrile compound>

[0075] The polymer (A) may contain repeating units (a7) derived from an α,β-unsaturated nitrile compound. The α,β-unsaturated nitrile compound is not particularly limited, and examples thereof include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethylacrylonitrile, vinylidene cyanide, and the like, and one or more selected from these may be used. Among these, one or more selected from acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is particularly preferred.

[0076] When the total amount of repeating units contained in the polymer (A) is 100% by mass, the content of the repeating unit (a7) derived from the α,β-unsaturated nitrile compound is preferably 0 to 10% by mass, and more preferably 1 to 8% by mass. By containing the repeating unit (a8) within the above range, the polymer (A) can sometimes improve the affinity with the electrolyte of the polymer (A), facilitate the insertion and removal of Li ions, and show good charge and discharge characteristics.

[0077] <Repeating unit (a8) derived from a compound having a sulfonic acid group>

[0078] The polymer (A) may contain repeating units (a8) derived from a compound having a sulfonic acid group. The compound having a sulfonic acid group is not particularly limited, and examples thereof include vinyl sulfonic acid, styrene sulfonic acid, allyl sulfonic acid, (meth) sulfoethyl acrylate, (meth) sulfopropyl acrylate, (meth) sulfobutyl acrylate, 2-acrylamide-2-methylpropane sulfonic acid, acrylamide tert-butyl sulfonic acid, 2-hydroxy-3-acrylamide propane sulfonic acid, 3-allyloxy-2-hydroxypropane sulfonic acid and the like, and alkali salts thereof, and one or more selected from these may be used.

[0079] When the total of the repeating units contained in the polymer (A) is set to 100% by mass, the content ratio of the repeating unit (a8) derived from the compound having a sulfonic acid group is preferably 0 to 10% by mass, and more preferably 1 to 6% by mass. By containing the repeating unit (a8) within the above range, the polymer (A) can produce an active material layer and a protective film with good dispersibility and homogeneity of the active material and filler, so that sometimes the structural defects of the electrode plate disappear, showing good charge and discharge characteristics.

[0080] <Repeating unit derived from cationic monomer>

[0081] The polymer (A) may contain repeating units derived from a cationic monomer. The cationic monomer is not particularly limited, but is preferably at least one monomer selected from a secondary amine (salt), a tertiary amine (salt) and a quaternary ammonium salt. The cationic monomer is not particularly limited, and examples thereof include 2-(dimethylamino)ethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate methyl chloride quaternary salt, 2-(diethylamino)ethyl (meth)acrylate, 3-(dimethylamino)propyl (meth)acrylate, 3-(diethylamino)propyl (meth)acrylate, 4-(dimethylamino)phenyl (meth)acrylate, 2-[(3,5-dimethylpyrazole)carbonylamino]ethyl (meth)acrylate, 2-(0-[1'-methylpropyleneamino]carbonylamino)ethyl (meth)acrylate, 2-(1-aziridinyl)ethyl (meth)acrylate, methacryloylcholine chloride, tris(2-propyleneamino)isocyanurate, The present invention also includes 1,2-di(2-pyridyl)ethylene, 4'-hydrazino-2-stilbeneazole dihydrochloride hydrate, 4-(4-dimethylaminostyryl)quinoline, 1-vinylimidazole, diallylamine, diallylamine hydrochloride, triallylamine, diallyldimethylammonium chloride, dichloroallylamine, N-allylbenzylamine, N-allylaniline, 2,4-diamino-6-diallylamino-1,3,5-triazine, N-trans-cinnamyl-N-methyl-(1-naphthylmethyl)amine hydrochloride, trans-N-(6,6-dimethyl-2-heptene-4-ynyl)-N-methyl-1-naphthylmethylamine hydrochloride, and the like. At least one selected from these can be used.

[0082] 1.1.2. Physical properties of polymer (A)

[0083] Dynamic viscoelasticity

[0084] When the dynamic viscoelasticity of the polymer (A) is measured by the following measurement method, the peak top of tan δ (loss elastic modulus / storage elastic modulus) appears only once in the range of -50°C to 0°C and only once in the range of 50°C to 150°C.

[0085] The sample for the dynamic viscoelasticity measurement is a film of polymer (A). The film of polymer (A) is prepared as follows: polymer (A) is dried at 40°C for 24 hours to prepare a uniform film with a thickness of 1.0±0.3 mm. The film is dried in a vacuum dryer at 160°C for 30 minutes, and then a strip of film of 10 mm×10 mm is cut out. Next, the following dynamic viscoelasticity measuring device is used to fix the sample with parallel plates (product name "PP-12"), and the measurement is performed according to the following measurement conditions in the temperature range of -70°C to 180°C. From the obtained graph of the temperature dependence of tanδ (loss elastic modulus / storage elastic modulus), the peak temperature Tp1 (°C) on the low temperature side and the peak temperature Tp2 (°C) on the high temperature side of the peak temperature of tanδ are respectively calculated.

[0086] ·Measurement conditions: Shear mode, measurement frequency 0.01~1Hz, heating rate 0.1℃ / min

[0087] Dynamic viscoelasticity measuring device: Anton Paar, model "MCR 301"

[0088] In the peak of tanδ measured by the dynamic viscoelasticity of the polymer (A), the peak temperature Tp1 (°C) on the low temperature side is preferably present in the following temperature range: preferably -50°C to 0°C, more preferably -48°C to -3°C, and particularly preferably -45°C to -5°C. The presence of one peak in the above temperature range indicates high viscosity in the same temperature range. It is believed that due to the high viscosity, the high adhesion of the polymer (A) in the same temperature range can be maintained, and good adhesion can be exhibited. It is further believed that the flexibility of the electrode can also be improved, and a storage device showing good charge and discharge characteristics can be obtained.

[0089] The peak temperature Tp2 (°C) on the high temperature side of the peak of tanδ measured by the dynamic viscoelasticity of the polymer (A) is preferably present in the following temperature range: preferably 50°C to 150°C, more preferably 60°C to 145°C, and particularly preferably 70°C to 140°C. The presence of one peak in the above temperature range indicates that a polymer with a uniform crosslinking composition is formed in the same temperature range. It is believed that due to the high viscosity, the uniform crosslinking composition of the polymer (A) in the same temperature range is large, indicating the hardness of the polymer (A) and reducing the increase in internal resistance.

[0090] Examples of methods for adjusting the peak top temperatures Tp1 and Tp2 of tan δ include methods of adjusting the monomer composition during polymerization of the polymer (A).

[0091] 1.1.2.2. Electrolyte swelling rate

[0092] The swelling rate (also referred to as "electrolyte swelling rate" in this specification) when the polymer (A) is immersed in a solvent consisting of propylene carbonate and diethyl carbonate in a volume fraction of 1:1 at 70°C for 24 hours is preferably 120% to 300% by mass, more preferably 130% to 280% by mass, and particularly preferably 140% to 250% by mass. If the electrolyte swelling rate of the polymer (A) is within the above range, the polymer (A) can swell moderately by absorbing the electrolyte. As a result, the solvated lithium ions can easily reach the active material. Furthermore, if the electrolyte swelling rate is within the above range, the coverage of the active material of the polymer (A) becomes lower, the electrode resistance is effectively reduced, and good charge and discharge characteristics are shown.

[0093] 1.1.2.3. Number average particle size

[0094] When polymer (A) exists as particles, the number average particle size of the particles is preferably 50nm to 500nm, more preferably 60nm to 450nm, and particularly preferably 70nm to 400nm. If the number average particle size of the particles of polymer (A) is within the above range, the particles of polymer (A) become easily adsorbed on the surface of the active material, so along with the movement of the active material, the particles of polymer (A) can also follow the movement. As a result, migration can be suppressed, so sometimes the degradation of electrical properties can be reduced. The number average particle size of polymer (A) can be measured by the method described in the examples described later.

[0095] 1.1.2.4. Surface acidity

[0096] When the polymer (A) exists as particles, the surface acid amount of the particles is preferably 0.05mmol / g to 2mmol / g, more preferably 0.1mmol / g to 1.8mmol / g, and particularly preferably 0.15mmol / g to 1.5mmol / g. If the surface acid amount of the particles of the polymer (A) is within the above range, a stable and homogeneous slurry can be prepared. If such a homogeneous slurry is used to prepare an active material layer, an active material layer in which the particles of the active material and the polymer (A) are uniformly dispersed and the thickness deviation is small can be obtained. As a result, the deviation of the charge and discharge characteristics in the electrode can be suppressed, so that a storage device showing good charge and discharge characteristics can be obtained. The surface acid amount of the polymer (A) can be measured by the method described in the examples described later.

[0097] 1.1.3. Method for producing polymer (A)

[0098] <Polymerization process>

[0099] The method for producing the polymer (A) is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization can be used. As the polymerization reaction, any reaction such as ion polymerization, free radical polymerization, and active free radical polymerization can be used. As the polymerization initiator used for the polymerization, for example, organic peroxides such as lauroyl peroxide, diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, tert-butyl peroxypivalate, and 3,3,5-trimethylhexanoyl peroxide; azo compounds such as α,α'-azobisisobutyronitrile; ammonium persulfate, potassium persulfate, etc. can be cited.

[0100] Among the above-mentioned polymerization methods, for example, an emulsion polymerization method performed in the presence of a known emulsifier, chain transfer agent, polymerization initiator, and the like is preferred.

[0101] As the emulsifier used in the emulsion polymerization method, there can be mentioned anionic surfactants such as sulfate esters of higher alcohols, alkylbenzene sulfonates, alkylnaphthalene sulfonates, alkyldiphenyl ether disulfonates, aliphatic sulfonates, aliphatic carboxylates, dehydroabietic acid salts, naphthalenesulfonic acid·formaldehyde condensates, and sulfate esters of nonionic surfactants; nonionic surfactants such as alkyl esters of polyethylene glycol, alkylphenyl ethers of polyethylene glycol, and alkyl ethers of polyethylene glycol; fluorine-based surfactants such as perfluorobutyl sulfonates, perfluoroalkyl-containing phosphates, perfluoroalkyl-containing carboxylates, and perfluoroalkyl ethylene oxide adducts, and the like, and one or more selected from these can be used.

[0102] As the chain transfer agent and the polymerization initiator used in the emulsion polymerization method, compounds described in Japanese Patent No. 5999399 and the like can be used.

[0103] The emulsion polymerization method for synthesizing the polymer (A) may be carried out in a single stage or in a multi-stage polymerization of two or more stages.

[0104] When the polymer (A) is synthesized by one-stage polymerization, the monomer mixture can be subjected to emulsion polymerization preferably at 40 to 80° C. for 4 to 36 hours in the presence of a suitable emulsifier, chain transfer agent, polymerization initiator, etc.

[0105] When the polymer (A) is synthesized by two-stage polymerization, the polymerization in each stage is preferably set as follows.

[0106] The ratio of the monomers used in the first stage polymerization is preferably in the range of 20 to 99% by mass, and more preferably in the range of 25 to 99% by mass, relative to the total mass of the monomers (the sum of the mass of the monomers used in the first stage polymerization and the mass of the monomers used in the second stage polymerization). By performing the first stage polymerization with such a ratio of monomers, particles of the polymer (A) having excellent dispersion stability and being difficult to produce coagulation can be obtained, and the viscosity increase of the binder composition for storage devices over time can be suppressed, so it is preferred.

[0107] The types and proportions of the monomers used in the second stage polymerization may be the same as or different from those used in the first stage polymerization.

[0108] From the viewpoint of the dispersibility of the particles of the obtained polymer (A), the polymerization conditions in each step are preferably set as follows.

[0109] · First stage polymerization: preferably a temperature of 40 to 80° C., preferably a polymerization time of 2 to 36 hours, preferably a polymerization conversion rate of 50% by mass or more, more preferably 60% by mass or more.

[0110] Second stage polymerization: preferably, the temperature is 40 to 80° C., and the polymerization time is preferably 2 to 18 hours.

[0111] By setting the total solid content concentration of the emulsion polymerization to 50% by mass or less, the polymerization reaction can be carried out in a state where the dispersion stability of the obtained polymer (A) particles is good. The total solid content concentration is preferably 48% by mass or less, and more preferably 45% by mass or less.

[0112] Regardless of whether the synthesis of polymer (A) is carried out as a one-stage polymerization or a two-stage polymerization method, it is preferred to add a neutralizing agent to the polymerization mixture after the emulsion polymerization is completed, thereby adjusting the pH to about 4.5 to 10.5, preferably 5 to 10, and more preferably 5.5 to 9.5. The neutralizing agent used here is not particularly limited, and examples thereof include metal hydroxides such as sodium hydroxide and potassium hydroxide; ammonia, etc. By setting the pH range as described above, the stability of polymer (A) is good. After the neutralization treatment, by concentrating the polymerization mixture, the solid content concentration can be increased while maintaining the good stability of polymer (A).

[0113] 1.1.4. Content ratio of polymer (A)

[0114] The content of the polymer (A) in the electrical storage device binder composition according to the present embodiment is preferably 10 to 100% by mass, more preferably 20 to 95% by mass, and particularly preferably 25 to 90% by mass in 100% by mass of the polymer component. Here, the polymer component may contain, in addition to the polymer (A), a polymer other than the polymer (A) described below, and a thickener, etc.

[0115] 1.2. Liquid medium (B)

[0116] The binder composition for storage device involved in the present embodiment contains a liquid medium (B). As the liquid medium (B), it is preferably an aqueous medium containing water, more preferably water. The above-mentioned aqueous medium can contain a non-aqueous medium other than water. As the non-aqueous medium, for example, amide compounds, hydrocarbons, alcohols, ketones, esters, amine compounds, lactones, sulfoxides, sulfone compounds, etc. can be cited, and one or more selected from these can be used. The binder composition for storage device involved in the present embodiment uses an aqueous medium as the liquid medium (B), so that the degree of negative impact on the environment is reduced, and the safety of the operator is also increased.

[0117] The content ratio of the non-aqueous medium contained in the aqueous medium is preferably 10% by mass or less, more preferably 5% by mass or less, and particularly preferably substantially free of the non-aqueous medium in 100% by mass of the aqueous medium. Here, "substantially free of the non-aqueous medium" means that the non-aqueous medium is not intentionally added as a liquid medium, and the non-aqueous medium that is inevitably mixed in when preparing the binder composition for storage devices may be contained.

[0118] 1.3. Other additives

[0119] The binder composition for an electrical storage device according to the present embodiment may contain additives other than the above-mentioned components as necessary. Examples of such additives include polymers other than the polymer (A), preservatives, thickeners, and the like.

[0120] 1.3.1. Polymers other than polymer (A)

[0121] The storage device binder composition involved in the present embodiment may contain polymers other than polymer (A). As such a polymer, it is not particularly limited, and unsaturated carboxylic acid esters or their derivatives can be cited as constituent units and contain acrylic polymers, PVDF (polyvinylidene fluoride) and other fluorine-based polymers, etc. These polymers can be used alone or in combination of more than two. By containing these polymers, flexibility and adhesion are sometimes further improved.

[0122] 1.3.2. Preservatives

[0123] The binder composition for storage devices according to the present embodiment may contain an antiseptic. By containing an antiseptic, the proliferation of bacteria, molds, etc. and the generation of foreign matter when the binder composition for storage devices is stored can sometimes be suppressed. As specific examples of the antiseptic, compounds described in Patent Gazette No. 5477610 and the like can be cited.

[0124] 1.3.3. Thickener

[0125] The electrical storage device binder composition according to the present embodiment may contain a thickener. By containing a thickener, the coating properties of the slurry, the charge and discharge characteristics of the obtained electrical storage device, etc. may be further improved.

[0126] Specific examples of thickeners include cellulose compounds such as carboxymethyl cellulose, methyl cellulose, and hydroxypropyl cellulose; polysaccharides such as alginic acid; poly(meth)acrylic acid; ammonium salts or alkali metal salts of the above cellulose compounds or poly(meth)acrylic acid; polyvinyl alcohol (co)polymers such as polyvinyl alcohol, modified polyvinyl alcohol, and ethylene-vinyl alcohol copolymers; and water-soluble polymers such as saponified copolymers of unsaturated carboxylic acids and vinyl esters such as (meth)acrylic acid, maleic acid, and fumaric acid. Among these, alkali metal salts of carboxymethyl cellulose and alkali metal salts of poly(meth)acrylic acid are preferred.

[0127] Examples of commercially available products of these thickeners include alkali metal salts of carboxymethylcellulose such as CMC1120, CMC1150, CMC2200, CMC2280, and CMC2450 (all manufactured by Daicel Corporation).

[0128] When the electrical storage device binder composition according to the present embodiment contains a thickener, the content of the thickener is preferably 5% by mass or less, more preferably 0.1 to 3% by mass, based on 100% by mass of the total solid content of the electrical storage device binder composition.

[0129] 1.4. pH of the binder composition for an electrical storage device

[0130] The pH of the binder composition for a storage device according to the present embodiment is preferably 4.5 to 10.5, more preferably 5 to 10, and particularly preferably 5.5 to 9.5. If the pH is within the above range, problems such as insufficient leveling and liquid dripping can be suppressed, and it is easy to manufacture a storage device electrode having both good electrical properties and good adhesion.

[0131] The "pH" in this specification refers to a physical property measured in the following manner. It is a value measured at 25°C using a pH meter using a glass electrode in accordance with JIS Z 8802:2011. The glass electrode is calibrated using a neutral phosphate standard solution and a borate standard solution as pH standard solutions. Examples of such a pH meter include "HM-7J" manufactured by DKK Toa Co., Ltd. and "D-51" manufactured by Horiba, Ltd.

[0132] It should be noted that, although it cannot be denied that the pH of the binder composition for a storage device is affected by the monomer composition constituting the polymer (A), it is not determined only by the monomer composition. That is, in general, it is known that even with the same monomer composition, the pH of the binder composition for a storage device will change due to polymerization conditions, etc., and the embodiments of the present application specification are just one example.

[0133] For example, even with the same monomer composition, the amount of carboxyl groups derived from the unsaturated carboxylic acid exposed on the surface of the obtained polymer is different when the unsaturated carboxylic acid is added to the polymerization reaction liquid in its entirety from the beginning and then other monomers are added in sequence, and when the monomers other than the unsaturated carboxylic acid are added to the polymerization reaction liquid and the unsaturated carboxylic acid is added last. It is believed that the pH of the binder composition for storage devices is greatly different even if only the order of adding monomers is changed in the polymerization method.

[0134] 2. Slurry for power storage equipment

[0135] The slurry for storage device involved in one embodiment of the present invention contains the above-mentioned binder composition for storage device. The above-mentioned binder composition for storage device can be used as a material for making a protective film, and the above-mentioned protective film is used to suppress the short circuit caused by the dendrites generated by charging and discharging, and can also be used as a material for making storage device electrodes (active material layers), and the above-mentioned storage device electrodes (active material layers) improve the binding ability of active materials to each other and the adhesion ability of active materials to collectors, as well as the anti-powdering property. Therefore, the slurry for storage device used to make a protective film (hereinafter also referred to as "slurry for protective film") and the slurry for storage device used to make the active material layer of the storage device electrode (hereinafter also referred to as "slurry for storage device electrodes") are described separately.

[0136] 2.1. Slurry for protective film

[0137] “Protective film slurry” refers to a dispersion used to make a protective film on the surface of an electrode, a separator, or both of them after being applied to the surface of the electrode, the separator, or both of them and then dried. The protective film slurry involved in this embodiment may be composed only of the above-mentioned binder composition for the storage device, and may also contain an inorganic filler. As an inorganic filler, an inorganic filler described in Japanese Patent Gazette No. 2020-184461 can be cited.

[0138] 2.2. Slurry for electrodes of power storage devices

[0139] "Electric storage device electrode slurry" refers to a dispersion used to prepare an active material layer on the surface of a current collector by coating it on the surface of a current collector and then drying it. The electrical storage device electrode slurry involved in this embodiment contains the above-mentioned electrical storage device binder composition and an active material. The components that can be contained in the electrical storage device electrode slurry involved in this embodiment are described below.

[0140] 2.2.1. Polymer (A)

[0141] The composition, physical properties, production method and the like of the polymer (A) are as described above, and therefore description thereof will be omitted.

[0142] The content ratio of the polymer component in the slurry for storage device electrodes according to the present embodiment is preferably 1 to 8 parts by mass, more preferably 1 to 7 parts by mass, and particularly preferably 1.5 to 6 parts by mass relative to 100 parts by mass of the active material. If the content ratio of the polymer component is within the above range, the dispersibility of the active material in the slurry is good and the coating property of the slurry is also excellent. Here, the polymer component includes a polymer (A), a polymer other than the polymer (A) added as needed, and a thickener, etc.

[0143] 2.2.2. Active substances

[0144] The active material used in the slurry for the storage device electrode according to the present embodiment may include a positive electrode active material and a negative electrode active material. Specific examples thereof include carbon materials, silicon materials, oxides containing lithium atoms, sulfur compounds, lead compounds, tin compounds, arsenic compounds, antimony compounds, aluminum compounds, polyacene and other conductive polymers; X B Y O Z(wherein A is an alkali metal or a transition metal, B is at least one selected from transition metals such as cobalt, nickel, aluminum, tin, and manganese, O represents an oxygen atom, and X, Y, and Z are numbers in the range of 1.10>X>0.05, 4.00>Y>0.85, and 5.00>Z>1.5, respectively.) A composite metal oxide or other metal oxide represented by. As specific examples thereof, compounds described in Patent Gazette No. 5999399, etc. can be cited.

[0145] The slurry for electrical storage device electrodes according to the present embodiment can be used when producing any electrical storage device electrode, i.e., a positive electrode or a negative electrode, and is particularly preferably used for a positive electrode.

[0146] The lithium ion secondary battery electrode produced by using the storage device electrode slurry according to the present embodiment can show good electrical properties even when an oxide containing lithium atoms is used as a positive electrode active material. The reason for this is that the polymer (A) can firmly adhere to the oxide containing lithium atoms and can maintain a state of firmly adhering to the oxide containing lithium atoms even during charge and discharge.

[0147] Examples of the oxide containing lithium atoms include at least one selected from lithium atom-containing oxides (olivine-type lithium-containing phosphate compounds) represented by the following general formula (1) and having an olivine-type crystal structure.

[0148] Li 1-x M x (AO4)·····(1)

[0149] (In formula (1), M is at least one metal ion selected from Mg, Ti, V, Nb, Ta, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, Ge, and Sn, A is at least one metal ion selected from Si, S, P, and V, and x satisfies the relationship of 0<x<1.)

[0150] The value of x in the general formula (1) is selected based on the valences of M and A so that the valence of the general formula (1) as a whole becomes 0.

[0151] Examples of the olivine-type lithium-containing phosphate compound include LiFePO4, LiCoPO4, LiMnPO4, Li 0.9 0Ti 0.05 Nb 0.05 Fe 0.30 Co 0.30 Mn 0.30 PO4, etc. Among these, LiFePO4 (lithium iron phosphate) is particularly preferred because the iron compound serving as the raw material is easily available and inexpensive.

[0152] The average particle size of the olivine-type lithium-containing phosphate compound is preferably in the range of 1 to 30 μm, more preferably in the range of 1 to 25 μm, and particularly preferably in the range of 1 to 20 μm.

[0153] In addition, the active material layer may contain the following active materials. For example, conductive polymers such as polyphenylene may be mentioned; X B Y O Z (Wherein, A is an alkali metal or a transition metal, B is at least one selected from transition metals such as cobalt, nickel, aluminum, tin, and manganese, O represents an oxygen atom, and X, Y, and Z are numbers in the range of 1.10>X>0.05, 4.00>Y>0.85, and 5.00>Z>1.5, respectively.) A composite metal oxide or other metal oxide represented by the above.

[0154] Examples of the composite metal oxide include lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, and ternary nickel-cobalt-manganese oxide.

[0155] The storage device electrode produced using the storage device electrode slurry according to the present embodiment can show good electrical properties even when an oxide containing lithium atoms is used as a positive electrode active material. The reason for this is that the polymer (A) can firmly bind the oxide containing lithium atoms and maintain the state of firmly binding the oxide containing lithium atoms even during charge and discharge.

[0156] On the other hand, when making a negative electrode, a mixture of silicon material and carbon material is also preferred in the above-exemplified active material. The volume change of carbon material with charge and discharge is smaller than that of silicon material, so by using a mixture of silicon material and carbon material as a negative electrode active material, the influence of the volume change of silicon material can be alleviated, and the adhesion of the active material layer to the collector can be further improved.

[0157] 2.2.3. Other ingredients

[0158] In the slurry for storage device electrodes involved in this embodiment, in addition to the above-mentioned components, other components can be added as needed. As such components, for example, polymers other than polymer (A), thickeners, liquid media, conductive aids, pH adjusters, preservatives, cellulose fibers, etc. can be cited. As polymers and thickeners other than polymer (A), they can be appropriately selected from the compounds exemplified in the above-mentioned item "1.3. Other additives" and used for the same purpose and content ratio.

[0159] <Liquid medium>

[0160] In the slurry for storage device electrodes according to the present embodiment, in addition to the portion introduced from the storage device binder composition, a liquid medium may be further added. The added liquid medium may be the same type as the liquid medium (B) contained in the storage device binder composition, or may be different, and is preferably selected and used from the liquid medium exemplified in the above-mentioned item "1.2. Liquid medium (B)".

[0161] The content ratio of the liquid medium (including the portion introduced from the binder composition for a storage device) in the storage device electrode slurry involved in this embodiment is preferably a solid content concentration in the slurry (the ratio of the total mass of the components other than the liquid medium in the slurry to the total mass of the slurry. The same applies hereinafter) of 30 to 70 mass %, more preferably 40 to 60 mass %.

[0162] <Conductive additive>

[0163] A conductive auxiliary agent may be further added to the slurry for electrical storage device electrodes according to the present embodiment for the purpose of imparting conductivity and buffering the volume change of the active material due to the entry and exit of lithium ions.

[0164] Specific examples of conductive aids include activated carbon, acetylene black, Ketjen black, furnace black, graphite, carbon fiber, fullerene, carbon nanotubes and the like. Of these, acetylene black or carbon nanotubes can be preferably used. The content of the conductive agent is preferably 20 parts by mass or less, more preferably 1 to 15 parts by mass, and particularly preferably 2 to 10 parts by mass relative to 100 parts by mass of the active material.

[0165] <pH adjuster and preservative>

[0166] For the purpose of suppressing corrosion of the current collector depending on the type of active material, a pH adjuster and / or an antiseptic may be further added to the slurry for electrical storage device electrodes according to the present embodiment.

[0167] As the pH adjusting agent, for example, hydrochloric acid, phosphoric acid, sulfuric acid, acetic acid, formic acid, ammonium phosphate, ammonium sulfate, ammonium acetate, ammonium formate, ammonium chloride, sodium hydroxide, potassium hydroxide, etc. can be cited, among which sulfuric acid, ammonium sulfate, sodium hydroxide, potassium hydroxide are preferred. In addition, it is also possible to select and use the neutralizing agent described in the production method of the polymer (A).

[0168] Examples of the preservative include ammonium metavanadate, sodium metavanadate, potassium metavanadate, ammonium metatungstate, sodium metatungstate, potassium metatungstate, ammonium paratungstate, sodium paratungstate, potassium paratungstate, ammonium molybdate, sodium molybdate, and potassium molybdate. Among these, ammonium paratungstate, ammonium metavanadate, sodium metavanadate, potassium metavanadate, and ammonium molybdate are preferred.

[0169] <Cellulose fiber>

[0170] Cellulose fibers may be further added to the slurry for storage device electrodes according to the present embodiment. By adding cellulose fibers, the adhesion of the active material to the current collector can sometimes be improved. It is believed that the fibrous cellulose fibers can closely adhere adjacent active materials to each other in a fibrous manner through line bonding or line contact, thereby preventing the active material from falling off and improving the adhesion to the current collector.

[0171] 2.2.4. Preparation method of slurry for storage device electrodes

[0172] The slurry for the storage device electrode involved in this embodiment can be manufactured by any method as long as it contains the above-mentioned storage device binder composition and active material. From the viewpoint of more efficiently and cheaply manufacturing a slurry with better dispersibility and stability, it is preferred to add active materials and any additional components used as needed to the above-mentioned storage device binder composition, and mix them to manufacture. As a specific manufacturing method, for example, the method described in Patent Gazette No. 5999399 can be cited.

[0173] 3.Electrodes for power storage devices

[0174] The storage device electrode involved in one embodiment of the present invention comprises a collector and an active material layer formed by applying the storage device electrode slurry on the surface of the collector and drying it. The storage device electrode can be manufactured by applying the storage device electrode slurry on the surface of a collector such as a metal foil to form a coating film, and then drying the coating film to form an active material layer. The storage device electrode manufactured in this way is formed by bonding an active material layer to the surface of the collector, and the active material layer contains the polymer (A), an active material, and any components added as needed, so that a storage device with excellent adhesion and flexibility, reduced internal resistance increase, and excellent cycle characteristics can be obtained.

[0175] The current collector is not particularly limited as long as it is made of a conductive material, and examples thereof include current collectors described in Japanese Patent No. 5999399 and the like.

[0176] 4. Electricity storage equipment

[0177] The storage device according to one embodiment of the present invention comprises the storage device electrode described above and an electrolyte, and can be manufactured by using components such as separators and in accordance with conventional methods. As a specific manufacturing method, for example, the following method can be cited: overlapping the negative electrode and the positive electrode via a separator, winding, folding, etc. according to the shape of the battery and storing them in a battery container, injecting the electrolyte into the battery container and sealing it, etc. The shape of the battery can be a suitable shape such as a button type, a cylindrical type, a square type, a stacked type, etc.

[0178] The electrolyte may be in liquid or gel form. Depending on the type of active material, an electrolyte that effectively functions as a battery may be selected from known electrolytes used in power storage devices. The electrolyte may be a solution formed by dissolving an electrolyte in an appropriate solvent. For such electrolytes and solvents, for example, compounds described in Patent Gazette No. 5999399 may be cited.

[0179] The above-mentioned power storage device can be applied to lithium ion secondary batteries, double electric layer capacitors, lithium ion capacitors, etc. that need to be discharged at a large current density. Among these, lithium ion secondary batteries are particularly preferred. In the power storage device electrode and power storage device involved in this embodiment, the parts other than the power storage device binder composition can use known parts for lithium ion secondary batteries, double electric layer capacitors, and lithium ion capacitors.

[0180] 5. Examples

[0181] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. "Parts" and "%" in Examples and Comparative Examples are based on mass unless otherwise specified.

[0182] 5.1. Example 1

[0183] 5.1.1. Preparation of binder composition for power storage device

[0184] In a 7-liter separable flask, 90 parts by mass of water and 0.2 parts by mass of sodium dodecylbenzenesulfonate were added, and 15 parts by mass of n-butyl acrylate (BA), 1 part by mass of allyl methacrylate (AMA), and 5 parts by mass of styrene (ST) as monomers were fully stirred to prepare a monomer emulsion containing a mixture of the above monomers.

[0185] The temperature inside the above-mentioned separable flask was started to rise, and when the temperature inside reached 60°C, 0.5 parts by mass of ammonium persulfate as a polymerization initiator was added. Then, the temperature of the separable flask was raised to 70°C, and polymerization was carried out for 6 hours. After confirming that the conversion rate exceeded 80%, 60 parts by mass of water and 0.3 parts by mass of sodium dodecylbenzenesulfonate were added, and 1 part by mass of allyl methacrylate (AMA), 68 parts by mass of styrene (ST), 5 parts by mass of acrylic acid (AA), and 5 parts by mass of acrylonitrile (AN) as monomers were fully stirred, and a monomer emulsion containing the above-mentioned monomer mixture was slowly added over 3 hours. Then, the temperature inside the separable flask was raised to 85°C, and this temperature was maintained for 3 hours to carry out polymerization reaction. After 3 hours, the separable flask was cooled to stop the reaction, and then an aqueous sodium hydroxide solution was added to adjust the pH to 8.0, thereby obtaining an aqueous dispersion containing 40% by mass of particles composed of polymer (A).

[0186] 5.1.2. Evaluation of physical properties of polymer (A)

[0187] The dynamic viscoelasticity, electrolyte swelling ratio, pH, number average particle size, and surface acid content of the polymer (A) obtained above were measured according to the following method. In the measurement of pH, number average particle size, and surface acid content, the aqueous dispersion of the polymer (A) was used as the measurement sample. The results are shown in Table 1.

[0188] <Measurement of dynamic viscoelasticity>

[0189] The film of polymer (A) was used as a measurement sample for dynamic viscoelasticity measurement. Regarding the film of polymer (A), polymer (A) was dried at 40°C for 24 hours to prepare a uniform film with a thickness of 1.0±0.3 mm. The film was dried in a vacuum dryer at 160°C for 30 minutes, and then a 10 mm×10 mm strip film was cut out. Next, the following dynamic viscoelasticity measuring apparatus was used to fix the measurement sample using parallel plates (product name "PP-12"), and the measurement was performed in a temperature range of -70°C to 180°C according to the following measurement conditions. From the obtained graph of the temperature dependence of tanδ (loss elastic modulus / storage elastic modulus), the peak temperature Tp1 (°C) on the low temperature side and the peak temperature Tp2 (°C) on the high temperature side of the peak temperature of tanδ were respectively obtained.

[0190] ·Measurement conditions: shear mode, measurement frequency 1 Hz, heating rate 5°C / min

[0191] Dynamic viscoelasticity measuring device: Anton Paar, model "MCR 301"

[0192] <Determination of electrolyte swelling ratio>

[0193] The polymer (A) obtained above is dried in a thermostatic bath at 40°C for 24 hours to form a film. 1 g of the film is immersed in 20 mL of a mixed solution consisting of propylene carbonate (PC) and diethyl carbonate (DEC) (PC / DEC = 1 / 1 (volume ratio), hereinafter referred to as "PC / DEC"), and allowed to stand at 70°C for 24 hours. Next, the insoluble components are separated by filtration with a 300-mesh metal mesh, and the weight (Y (g)) of the residue obtained by evaporating the soluble PC / DEC is measured. In addition, the PC / DEC attached to the surface of the insoluble component (film) separated by the above filtration is absorbed on paper and removed, and the weight (Z (g)) of the insoluble component (film) is measured. The electrolyte swelling rate is calculated according to the following formula (2).

[0194] Electrolyte swelling ratio (mass %) = (Z / (1-Y)) × 100 (2)

[0195] <Measurement of pH>

[0196] The pH at 25° C. of the aqueous dispersion of the polymer (A) obtained above was measured using a pH meter (manufactured by Horiba, Ltd.).

[0197] <Determination of number average particle size>

[0198] A latex prepared by diluting the aqueous dispersion of the polymer (A) obtained above to 0.1 wt% was added by pipette to a collodion support membrane, and a 1 wt% phosphotungstic acid solution was added by pipette to a collodion support membrane, and air-dried for 12 hours to prepare a sample. The sample prepared in this way was observed using a transmission electron microscope (TEM, manufactured by Hitachi HighTechnologies, model "H-7650") at a magnification of 10K, and image analysis was performed according to the program of HITACHI EMIP to calculate the number average particle size of 50 randomly selected particles of the polymer (A).

[0199] <Measurement of surface acidity>

[0200] The surface acid amount of the particles of the polymer (A) obtained above is measured as follows. First, confirm that the reagent bottle on the upper part of the burette and main body of the potentiometric titration device (manufactured by Kyoto Electronics Co., Ltd., model "AT-510") is filled with 0.005 mol / L sulfuric acid, and confirm that the conductivity of ultrapure water is less than 2μS. Next, purge to exhaust the air in the burette, and further defoam the nozzle. Then, take the polymer (A) obtained above, which is about 1g in terms of solid content, into a 300mL beaker and record the sample weight. After adding ultrapure water to dilute to 200mL, add 1mol / L sodium hydroxide aqueous solution. When approaching the end point, stir for about 30 seconds to confirm that the conductivity is stable. Press the RESET button of the measurement program to form a measurement standby state. Press the START button of the measurement program to start the measurement using 0.005mol / L sulfuric acid. When the end point is reached, the process automatically ends and the file is saved. The obtained curve is analyzed and the surface acid amount is calculated from the amount of sulfuric acid used using the following formula (3).

[0201] Surface acid amount (mmol / g) = Amount of acid used in the carboxylic acid region on the particle surface [mL] × acid concentration [mol / L] × degree of ionization / sample weight [g] / 1000 (3)

[0202] 5.1.3. Preparation of slurry for positive electrode of non-aqueous secondary battery

[0203] Into a twin-shaft planetary mixer (manufactured by PRIMIX Co., Ltd., trade name "TKHIVIS MIX 2P-03"), 2 parts by mass of the above-mentioned polymer (A) (solid content conversion value, added as an aqueous dispersion of the above-obtained polymer (A)), 100 parts by mass of NMC622 (trade name "ME-8A", manufactured by Beijing Dangsheng Co., Ltd.) as a positive electrode active material, 5 parts by mass of acetylene black, 1 part by mass of a thickener (trade name "CMC2200", manufactured by Daicel Co., Ltd.), and 20 parts by mass of water were added, and stirred at 60 rpm for 1 hour.

[0204] Then, the mixture was stirred for 1 hour to obtain a paste. Water was added to the obtained paste to adjust the solid content concentration to 70%, and then the mixture was stirred and mixed at 200 rpm for 2 minutes, at 1800 rpm for 5 minutes, and further at a vacuum (about 5.0×10 3 The mixture was stirred and mixed at 1800 rpm for 1.5 minutes to prepare a slurry for a positive electrode of a non-aqueous secondary battery.

[0205] 5.1.4. Fabrication and physical property evaluation of positive electrodes for non-aqueous secondary batteries

[0206] 5.1.4.1. Fabrication of positive electrode for non-aqueous secondary batteries

[0207] The non-aqueous secondary battery positive electrode slurry obtained above was uniformly applied on the surface of a collector consisting of an aluminum foil having a thickness of 20 μm by a doctor blade method in such a manner that the film thickness after drying was 100 μm, and dried at 120° C. for 20 minutes. Then, the density of the formed film (positive electrode active material layer) was 3.0 g / cm 3 The positive electrode for a non-aqueous secondary battery was obtained by performing press processing using a roll press.

[0208] 5.1.4.2. Physical property evaluation of positive electrode for non-aqueous secondary batteries

[0209] <Evaluation of Adhesion Strength>

[0210] On the surface of the positive electrode for the non-aqueous secondary battery obtained above, a knife was used to cut 10 cuts from the active material layer to the depth of the collector at 2 mm intervals, making a checkerboard cut. An adhesive tape with a width of 18 mm (manufactured by NICHIBAN Co., Ltd., trade name "Cellotape" (registered trademark) JIS Z 1522: 2009 regulations) was attached to the cut and immediately peeled off, and the degree of shedding of the active material was determined and evaluated by visual observation. The evaluation criteria are as follows. The evaluation results are shown in Table 1.

[0211] (Evaluation Criteria)

[0212] 5 points: No active material layer was fallen off.

[0213] 4 points: 1 to 5 active material layers were detached.

[0214] · 3 points: 6 to 20 active material layers were detached.

[0215] · Point 2: 21 to 40 active material layers were detached.

[0216] 1 point: 41 or more active material layers were fallen off.

[0217] <Evaluation of rolling up>

[0218] The positive electrode for the non-aqueous secondary battery obtained above was punched out into a shape of 4 cm × 6 cm. The punched electrode was vacuum dried at 160°C for 6 hours. Then, the electrode was placed in a drying room, and the rupture of the electrode when bent at 180° was confirmed and evaluated by visual observation using a 0.514-Type1 coating flexure tester manufactured by Yasuda Seiki and the cylindrical mandrel method. The mandrel diameters used were φ4, φ5, φ6, φ8, φ10, φ12, φ16, φ20, φ25, and φ32 mm. The evaluation criteria are as follows. The evaluation results are shown in Table 1.

[0219] (Evaluation Criteria)

[0220] ·5 points: No cracking of the electrode occurs when the mandrel diameter is φ4 mm or less.

[0221] Point 4: No electrode cracking occurred at a mandrel diameter of φ5 mm, but electrode cracking occurred at a mandrel diameter of φ4 mm.

[0222] Point 3: No electrode cracking occurred at a mandrel diameter of φ12 mm, but electrode cracking occurred at a mandrel diameter of φ10 mm.

[0223] Point 2: No electrode cracking occurred at a mandrel diameter of φ25 mm, but electrode cracking occurred at a mandrel diameter of φ20 mm.

[0224] · Point 1: Cracks occurred in the electrode at a mandrel diameter of φ32 mm.

[0225] 5.1.5. Fabrication and physical property evaluation of non-aqueous secondary batteries

[0226] 5.1.5.1. Preparation of slurry for negative electrode of non-aqueous secondary battery and preparation of negative electrode for non-aqueous secondary battery

[0227] Into a twin-shaft planetary mixer (manufactured by PRIMIX Co., Ltd., trade name "TKHIVIS MIX 2P-03"), 1 part by mass (solid content conversion) of a thickener (trade name "CMC2200", manufactured by Daicel Co., Ltd.), 100 parts by mass (solid content conversion) of graphite as a negative electrode active material, and 68 parts by mass of water were added and stirred at 60 rpm for 1 hour.

[0228] Then, only SBR (trade name "TRD105A", manufactured by ENEOS Materials Co., Ltd.) was added in an amount equivalent to 2 parts by mass (in terms of solid content), and the mixture was further stirred for 1 hour to obtain a paste. Water was added to the obtained paste, and after adjusting the solid content to 50%, a stirring deaerator (manufactured by Thinky Co., Ltd., trade name "Degassing Rentaro") was used to stir and mix at 200 rpm for 2 minutes, at 1800 rpm for 5 minutes, and further at 1800 rpm for 1.5 minutes under vacuum to prepare a slurry for a negative electrode of a non-aqueous secondary battery.

[0229] Next, the non-aqueous secondary battery negative electrode slurry prepared above was evenly coated on the surface of a collector consisting of a copper foil with a thickness of 20 μm by a doctor blade method in a manner such that the film thickness after drying was 80 μm, and dried at 120°C for 20 minutes. Then, the density of the formed film (negative electrode active material layer) was 1.9 g / cm 3 The negative electrode for a non-aqueous secondary battery was obtained by pressurizing the obtained product using a roll press.

[0230] 5.1.5.2. Assembly of non-aqueous secondary batteries (lithium-ion batteries)

[0231] In a glove box replaced with Ar to a dew point of -80°C or less, the nonaqueous secondary battery negative electrode produced above was punched into a circular shape with a diameter of 16.16 mm and placed on a diode type button cell (manufactured by Hohsen Co., Ltd., trade name "HS Flatcell").

[0232] Next, a separator made of a polypropylene porous film punched into a circular shape with a diameter of 24 mm (manufactured by Celgard Co., Ltd., trade name "Celgard #2400") was placed on top of the negative electrode for the nonaqueous secondary battery.

[0233] After further injecting 500 μL of electrolyte in a way that does not enter the air, the non-aqueous secondary battery produced above is punched into a circular product with a diameter of 15.95 mm and placed on the separator, and the outer casing of the above-mentioned two-pole button unit is tightened and sealed with screws to assemble a lithium ion battery unit (an example of a non-aqueous secondary battery). The electrolyte used here is a solution in which LiPF6 is dissolved at a concentration of 1 mol / L in a solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 1 (mass ratio).

[0234] 5.1.5.3. Physical property evaluation of non-aqueous secondary batteries

[0235] <Evaluation of cycle characteristics>

[0236] For the non-aqueous secondary battery manufactured as described above, charging is started at a constant current (1.0C) in a thermostatic bath adjusted to 25°C. When the voltage becomes 4.2V, charging is continued at a constant voltage (4.2V). The moment when the current value reaches 0.01C is regarded as the end (cutoff) of charging. Then, discharging is started at a constant current (1.0C), and the moment when the voltage becomes 3.0V is regarded as the end (cutoff) of discharging, and the discharge capacity of the first cycle is calculated. Repeat the charge and discharge 100 times in this way. The capacity retention rate is calculated by the following formula (4) and evaluated according to the following benchmarks. The evaluation results are shown in Table 1.

[0237] Capacity retention rate (%) = (discharge capacity at the 100th cycle / discharge capacity at the 1st cycle) × 100 (4)

[0238] (Evaluation Criteria)

[0239] 5 points: Capacity retention rate is 95% or more.

[0240] · Point 4: The capacity retention rate is 90% or more and less than 95%.

[0241] · Point 3: The capacity retention rate is 85% or more and less than 90%.

[0242] · Point 2: The capacity retention rate is 80% or more and less than 85%.

[0243] ·1 point: The capacity retention rate is 75% or more and less than 80%.

[0244] 0 point: The capacity retention rate is less than 75%.

[0245] <Evaluation of resistance increase rate>

[0246] For the non-aqueous secondary battery manufactured as described above, charging is started by a constant current (1.0C) in a thermostatic bath adjusted to 25°C. When the voltage becomes 4.2V, charging is continued at a constant voltage (4.2V). The moment when the current value becomes 0.01C is regarded as the end (cutoff) of charging. Then, discharging is started by a constant current (0.05C), and the moment when the voltage becomes 3.0V is regarded as the end (cutoff) of discharging, and the discharge capacity of the 0th cycle is calculated. Charging is further started by a constant current (1.0C), and when the voltage becomes 4.2V, charging is continued at a constant voltage (4.2V), and the moment when the current value becomes 0.01C is regarded as the end (cutoff) of charging. Then, discharging is started by a constant current (1.0C), and the moment when the voltage becomes 3.0V is regarded as the end (cutoff) of discharging, and the discharge capacity of the 1st cycle is calculated. Repeat 100 times of charging and discharging. After charging and discharging were repeated 100 times, charging and discharging were performed in the same manner as in the 0th cycle, and the discharge capacity at the 101st time was evaluated. The resistance increase rate was calculated from the following formula (5) and evaluated based on the following criteria.

[0247] Resistance increase rate (%)

[0248] =(discharge capacity at the 101st cycle - discharge capacity at the 100th cycle) / (discharge capacity at the 0th cycle - discharge capacity at the 1st cycle)×100·····(5)

[0249] (Evaluation Criteria)

[0250] · 5 points: The resistance increase rate is 100% or more and less than 110%.

[0251] · Point 4: The resistance increase rate is 110% or more and less than 120%.

[0252] · Point 3: The resistance increase rate is 120% or more and less than 130%.

[0253] · Point 2: The resistance increase rate is 130% or more and less than 140%.

[0254] ·1 point: The resistance increase rate is 140% or more and less than 150%.

[0255] 0 point: The resistance increase rate is 150% or more.

[0256] It should be noted that in the measurement conditions, "1C" means the current value at which a cell with a certain capacitance is discharged at a constant current and reaches the end of discharge within 1 hour. For example, "0.1C" means the current value at which discharge is completed after 10 hours, and "10C" means the current value at which discharge is completed after 0.1 hours.

[0257] 5.2. Examples 2 to 11, Comparative Examples 1 to 6

[0258] In the above-mentioned item "5.1.1. Preparation of binder composition for electrical storage device", except that the types and amounts of each monomer were as described in Table 1 or Table 2, respectively, an aqueous dispersion containing 40% by mass of polymer particles was obtained in the same manner. Otherwise, a slurry for electrical storage device electrodes was prepared in the same manner as in Example 1, and electrical storage device electrodes and electrical storage devices were produced, respectively, and evaluated in the same manner as in Example 1.

[0259] 5.3. Examples 12 to 16, Comparative Examples 7 to 9

[0260] In the above-mentioned item "5.1.3. Preparation of slurry for positive electrode of non-aqueous secondary battery", except that the content ratio of polymer, CMC (trade name "CMC2200", manufactured by Daicel Co., Ltd.), and alginic acid (trade name "sodium alginate 80-120", manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was as shown in Table 3, a slurry for positive electrode of non-aqueous secondary battery was prepared in the same manner as in Example 1, and an electric storage device electrode and an electric storage device were prepared, respectively, and evaluated in the same manner as in Example 1. The results are shown in Table 3.

[0261] 5.4. Examples 17 to 18

[0262] In the above-mentioned item "5.1.5.1. Preparation of slurry for negative electrode of non-aqueous secondary battery and preparation of negative electrode for non-aqueous secondary battery", the slurry for negative electrode of non-aqueous secondary battery was prepared in the same manner as in Example 1, except that the content ratio of polymer and CMC (trade name "CMC2200", manufactured by Daicel Co., Ltd.) was as shown in Table 4, and the storage device electrode and storage device were prepared respectively, and evaluated in the same manner as in Example 1. The results are shown in Table 4.

[0263] 5.5. Evaluation results

[0264] Tables 1 to 4 show the compositions of the electrical storage device binder compositions, the evaluation results of the physical properties of the polymers, and the evaluation results of the electrical storage device electrodes and electrical storage devices.

[0265] Table 1

[0266]

[0267] Table 2

[0268]

[0269] In addition, the abbreviations of each monomer in Table 1 and Table 2 represent the following monomers. <Unsaturated carboxylic acid ester having an aliphatic hydrocarbon group>

[0270] ·2EHA: 2-Ethylhexyl acrylate

[0271] BA: n-butyl acrylate

[0272] ·BMA: n-butyl methacrylate

[0273] MMA: Methyl methacrylate

[0274] EA: Ethyl acrylate <aromatic vinyl compound>

[0275] ·ST:Styrene

[0276] ·DVB: divinylbenzene<unsaturated carboxylic acid>

[0277] TA: Itaconic acid

[0278] AA: Acrylic acid

[0279] ·MAA: Methacrylic acid <Multifunctional (meth)acrylate>

[0280] ·EDMA: Ethylene glycol dimethacrylate

[0281] ·AMA: Allyl methacrylate<Other unsaturated carboxylic acid esters>

[0282] ·HEMA: 2-Hydroxyethyl Methacrylate

[0283] ·HEA: 2-Hydroxyethyl Acrylate

[0284] ·GLM: Glyceryl monomethacrylate<(meth)acrylamide>

[0285] AAM: Acrylamide

[0286] ·MAM: Methacrylamide <α,β-unsaturated nitrile compound>

[0287] AN: Acrylonitrile <compounds with sulfonic acid groups>

[0288] ·NASS: Sodium styrene sulfonate

[0289] <Unsaturated carboxylic acid ester having an alicyclic hydrocarbon group>

[0290] ·CHMA: Cyclohexyl methacrylate

[0291] ·CHA: Cyclohexyl acrylate

[0292] Table 3

[0293]

[0294] Table 4

[0295]

[0296] As can be seen from Tables 1 to 2 above, it can be seen that the slurry for storage device electrodes prepared using the storage device binder composition of the present invention shown in Examples 1 to 11 can produce storage device electrodes with excellent adhesion and flexibility compared to the cases of Comparative Examples 1 to 6, and can reduce the increase in the internal resistance of the storage device and improve the cycle characteristics. As a reason for this, it is speculated that the temperature of Tp1 of the polymer (A) contained in the storage device binder composition of Examples 1 to 11 shown in Table 1 above is -50°C to 0°C, so that the storage device binder composition itself shows flexibility, and as a result, good adhesion strength and electrode flexibility are shown. In addition, the temperature of Tp2 of the polymer (A) is 50°C to 150°C, thereby suppressing the fusion of particles and suppressing the coverage of the active material, so that the insertion and removal of lithium ions becomes easy, and the permeability of the electrolyte between the active materials is not hindered, and it can become low resistance. It is speculated that the result of being able to show good adhesion strength and flexibility and low resistance is to show good charge and discharge characteristics.

[0297] From the results of Table 3 above, it can be seen that the non-aqueous secondary battery positive electrode slurry according to the present invention, which uses a polymer (A) and a thickener, can more appropriately bond the active materials to each other, and can well maintain the adhesion between the active material layer and the collector. In particular, the non-aqueous secondary battery positive electrode slurry shown in Example 13 can appropriately bond the active materials to each other, and can well maintain the adhesion between the active material layer and the collector, even if alginic acid is used as a thickener.

[0298] As can be seen from the results in Table 4 above, the non-aqueous secondary battery negative electrode slurry according to the present invention shown in Example 18 shows good results even when using a negative electrode active material. It is believed that the electrolyte affinity is improved, so the insertion and removal of Li ions into the negative electrode active material becomes easy, and the resistance is reduced, so good charge and discharge characteristics are shown.

[0299] The present invention is not limited to the above-mentioned embodiments, and various modifications are possible. The present invention includes a configuration in which the configuration described in the embodiments is the same as the actual configuration (for example, the function, method and result are the same configuration, or the purpose and effect are the same configuration). In addition, the present invention includes a configuration in which a part that is not essential to the configuration described in the above-mentioned embodiments is replaced with another configuration. Furthermore, the present invention also includes a configuration that has the same effect as the configuration described in the above-mentioned embodiments, or a configuration that can achieve the same purpose. Furthermore, the present invention also includes a configuration in which a known technology is added to the configuration described in the above-mentioned embodiments.

Claims

1. A binder composition for an electrical storage device, comprising a polymer (A) and a liquid medium (B), When the total amount of the repeating units contained in the polymer (A) is 100% by mass, the polymer (A) contains: 15 to 64% by mass of the repeating unit (a1) derived from an unsaturated carboxylic acid ester having an aliphatic hydrocarbon group, excluding an unsaturated carboxylic acid ester having an alicyclic hydrocarbon group, Repeating units (a2) derived from aromatic vinyl compounds: 35 to 84% by mass The peak top of tan δ, i.e., loss elastic modulus / storage elastic modulus, of the dynamic viscoelasticity of the polymer (A) appears only once in the range of -50°C to 0°C and only once in the range of 50°C to 150°C.

2. The binder composition for an electrical storage device according to claim 1, wherein The polymer (A) further contains 0.1 to 10% by mass of a repeating unit (a3) ​​derived from an unsaturated carboxylic acid.

3. The binder composition for an electrical storage device according to claim 1, wherein When the polymer (A) is immersed in a solvent composed of propylene carbonate and diethyl carbonate in a volume ratio of 1:1 at 70° C. for 24 hours, the swelling ratio of the electrolyte solution is 120% to 300% by mass.

4. The binder composition for an electrical storage device according to claim 1, wherein The polymer (A) is a polymer particle, The number average particle size of the polymer particles is 50 nm to 500 nm.

5. The binder composition for an electrical storage device according to claim 4, wherein The surface acid amount of the polymer particles is 0.05 mmol / g to 2 mmol / g. 6 . A slurry for electrical storage device electrodes, comprising the electrical storage device binder composition according to claim 1 and an active material.

7. The slurry for electrical storage device electrodes according to claim 6, wherein The active material contains at least one selected from the group consisting of an olivine-type lithium-containing phosphate compound, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, and ternary nickel-cobalt-manganese oxide.

8. The slurry for electrical storage device electrodes according to claim 6, wherein A carbon material is contained as the active material. 9 . An electrical storage device electrode comprising a current collector and an active material layer formed by applying the slurry for electrical storage device electrodes according to claim 6 onto a surface of the current collector and drying the slurry. 10 . An electric storage device comprising the electric storage device electrode according to claim 9 .

Citation Information

Patent Citations

  • Binder for battery binder solution, electrode mixture, electrode structure and battery

    JP1998298386A

  • Binder composition for power storage device

    JP2019194944A

  • Binder composition for power storage device, slurry for power storage device electrode, power storage device electrode, and power storage device

    JP2020184461A